Efektivitas Penggunaan Teknologi E-Commerce Dalam Memengaruhi Perkembangan Bisnis Pada Era Digital - Angraini, Riska; Padli Nasution, Muhammad Irwan (CV. ITTC INDONESIA, 2024)
The digital era has changed the techniques and management in producing and selling goods and services. Electronic commerce or often referred to as e-commerce is one of the trading systems applied through the internet network. In recent years, especially since the pandemic has changed the way we socialize, interact, and do business so that new innovations have emerged with the internet/online trading system. Currently, many people use the e-commerce system, especially small traders, because they get more satisfying and economical benefits in several aspects. Starting from saving time to minimal capital spent in addition to being a trading medium, e-commerce also participates in opening cooperation between traders, customer service and job vacancies. Now e-commerce continues to grow which has resulted in significant changes to the business world economy. In 2022, Bank Indonesia reported that e-commerce transactions reached Rp476.3 trillion, showing a growth of 18.8% compared to the previous year. This is a sign that e-commerce brings good effectiveness to the development of trade through digital systems.